Correction to "Does Trust Matter More in Virtual Teams? A Meta-Analysis of Trust and Team Effectiveness Considering Virtuality and Documentation as Moderators" by Breuer et al. (2016). (Journal of Applied Psychology, 2026)
The article focuses on correcting a statistical error in the meta-analysis examining the relationship between team trust and task performance in face-to-face (Ftf) and virtual teams (VT). The original study incorrectly calculated t values for categorical moderators by using an improper formula for the standard error, leading to erroneous conclusions about the significance of moderators such as team type (Ftf vs. VT), documentation of team interactions, and research design (cross-sectional vs. longitudinal). After correction, these moderators no longer show statistically significant differences in their effect on the trust-performance relationship. However, some moderators, including source of data and rating type, remain statistically significant. The authors of the original study do not agree with this correction.